2007
DOI: 10.1080/10715760600943900
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide and hydroxyl radicals mediate palmitate-induced cytotoxicity to hepatoma cells: Relation to mitochondrial permeability transition

Abstract: We studied the toxicological responses of a human hepatoblastoma cell line (HepG2/C3A) to various free fatty acids (FFA) in order to identify the relation between reactive oxygen species (ROS) production and mitochondrial permeability transition (MPT). Exposure to the saturated FFA, palmitate, led to a time-dependent ROS production and hydrogen peroxide release as well as a loss of mitochondrial potential. The cytotoxicity of palmitate was significantly reduced by treating with scavengers of hydrogen peroxide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 68 publications
9
56
0
Order By: Relevance
“…The aging-associated oxidative stress in the liver (Nakata et al 1996) was associated with ceramide elevation in the cells and could be mimicked by the dietetic saturated fatty acid supplementation to the adult animals (Nagle et al 2009). Exposure of palmitic acid to liver cells led to the timedependent reactive oxygen species (ROS) production (Strivastava and Chan 2007), ceramide accumulation (Wei et al 2006), apoptotic hepatocyte death, and development of hepatic insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The aging-associated oxidative stress in the liver (Nakata et al 1996) was associated with ceramide elevation in the cells and could be mimicked by the dietetic saturated fatty acid supplementation to the adult animals (Nagle et al 2009). Exposure of palmitic acid to liver cells led to the timedependent reactive oxygen species (ROS) production (Strivastava and Chan 2007), ceramide accumulation (Wei et al 2006), apoptotic hepatocyte death, and development of hepatic insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Palmitate is the most prevalent saturated fatty acid in circulation, and its level is further elevated in patients with NASH (37). The lipotoxic effect has been observed in pancreatic b-cells (47,93), cardiomyocytes (77,101), and hepatic cell lines (50,72,84,128,140,154). Molina et al, recently described a role for mitochondrial dynamics in the progression of the lipotoxic effect, or lipidinduced apoptosis, of FFA incubation in pancreatic b-cells (91).…”
Section: Metabolic Insult and Mitochondrial Dynamicsmentioning
confidence: 99%
“…Generation of oxidative stress is an important factor in lipotoxicity by virtue of its contribution to cellular stress signaling and interference with mitochondrial functions (Srivastava and Chan, 2007). In a recent report, palmitate was demonstrated to limit GSH synthesis by inhibition of cysteine transporter xCT and subsequently limited substrate supply (Srivastava and Chan, 2008).…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 99%
“…Thus, in addition to increasing intracellular levels of ROS, saturated fatty acids may also negatively affect the intracellular redox state by limiting the GSH-mediated oxidative defense. In particular, the ER (Borradaile et al, 2006a,b;Karaskov et al, 2006;Wei et al, 2006), mitochondrion (Maestre et al, 2003;Boudina et al, 2007;Srivastava and Chan, 2007;Koshkin et al, 2008), and lysosomes (Feldstein et al, 2004 were suggested as putative sites for lipotoxic stress induced by saturated free fatty acids. Finally, fatty acids were shown to induce apoptosis, an endpoint of lipotoxicity that is termed lipoapoptosis (Unger and Orci, 2002).…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 99%